2017
DOI: 10.1627/jpi.60.34
|View full text |Cite
|
Sign up to set email alerts
|

Gasification Characteristics of Aminobutyric Acid and Serine as Model Compounds of Proteins under Supercritical Water Conditions

Abstract: The gasification characteristics of aminobutyric acid and serine were determined under supercritical water conditions using a tubular flow reactor. A 1.0 wt% aqueous solution of these two amino acids was gasified at temperatures ranging from 400 to 650 and a pressure of 25 MPa with residence time of 86-222 s. The products were identified and quantified by gas chromatography, and the total organic carbon in the aqueous phase was also determined. The gasification characteristics were compared with those of glyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The highest CGE yield obtained from experimental work was 0.76 at 600 °C and a residence time of 50 s. The temperature accelerated the rate of gasification. This CGE trend is in accordance with the previous reports. , …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The highest CGE yield obtained from experimental work was 0.76 at 600 °C and a residence time of 50 s. The temperature accelerated the rate of gasification. This CGE trend is in accordance with the previous reports. , …”
Section: Resultssupporting
confidence: 94%
“…This CGE trend is in accordance with the previous reports. 15,35 3.3. Reaction Kinetics of POME Gasification in Supercritical Water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modernization and growing industrialization of the world has driven a rising in petroleum-derived fuel demand every year. On any other way, the endless consumption of fossil fuels can cause severe global warming due to the greenhouse gases released into the atmosphere [1][2]. Therefore, these disastrous effects have led many researchers worldwide to find out alternative fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Under the subcritical condition, the liquid state of water is maintained . Recent works of supercritical water gasification (SCWG) demonstrated that under the supercritical water condition all of the fluids become one phase. Therefore, water is a suitable solution for organic materials and gaseous products.…”
Section: Introductionmentioning
confidence: 99%